Well-designed teaching strategies in involving the students in learning English - Santi Prastiyowati; Sri Hartiningsih; Riza Elfana; Miftahul Hamim (English Learning Innovation, 2025)
Students’ involvement is essential in learning, as it fosters active participation and serves as a key indicator of success in classroom learning. This study aimed to explore the strategies applied by an experienced English teacher and identify the most effective approaches for enhancing student engagement in a private senior high school in Malang. A qualitative case study approach was employed, applying Miles and Huberman’s data analysis model. Data were collected through non-participative observation, structured interviews, and field notes. The findings revealed that the teacher implemented five main strategies: Communicative Language Teaching (CLT), Task-Based Language Teaching (TBLT), pronunciation practice within a modified CLT approach, cross-linguistic transfer and language games. It was recognized that these strategies fostered interaction, collaboration, and engagement, effectively increasing student involvement—especially among students with lower proficiency or special needs. However, interview data highlighted cross-linguistic transfer and language games as the most effective strategies from the teacher’s perspective. These findings suggest that while classroom dynamics support student engagement through structured activities, the teacher perceives linguistic transfer and interactive games as more impactful for student participation. This study underscores the importance of combining multiple instructional strategies to enhance student involvement in English language learning and highlights the value of using multiple data sources to gain a more comprehensive understanding of teaching effectiveness.